ANGPT2 and NOS3 polymorphisms and clinical outcome in advanced hepatocellular carcinoma patients receiving sorafenib - Marisi, Giorgia; Raimondi, Francesco (Cancers, 2019)
Sorafenib represents the standard of care for advanced hepatocellular carcinoma (HCC), even though a large number of patients have reported limited efficacy. The aim of the present study was to evaluate the prognostic value of single-nucleotide polymorphisms on angiopoietin-2 (ANGPT2) and endothelial-derived nitric oxide synthase (NOS3) genes in 135 patients with advanced HCC receiving sorafenib. Eight ANGPT2 polymorphisms were analyzed by direct sequencing in relation to overall survival (OS) and progression-free survival (PFS). In univariate analysis, ANGPT2rs55633437 and NOS3 rs2070744 were associated with OS and PFS. In particular, patients with ANGPT2rs55633437 TT/GT genotypes had significantly lower median OS (4.66 vs. 15.5 months, hazard ratio (HR) 4.86, 95% CI 2.73–8.67, p < 0.001) and PFS (1.58 vs. 6.27 months, HR 4.79, 95% CI 2.73–8.35, p < 0.001) than those homozygous for the G allele. Moreover, patients with NOS3 rs2070744 TC/CC genotypes had significantly higher median OS (15.6 vs. 9.1 months, HR 0.65, 95% CI 0.44–0.97; p = 0.036) and PFS (7.03 vs. 3.5 months, HR 0.43, 95% CI 0.30–0.63; p < 0.001) than patients homozygous for the T allele. Multivariate analysis confirmed these polymorphisms as independent prognostic factors. Our results suggest that ANGPT2rs55633437 and NOS3 rs2070744 polymorphisms could identify a subset of HCC patients more resistant to sorafenib.